2009
DOI: 10.2337/db08-0749
|View full text |Cite
|
Sign up to set email alerts
|

A Role for von Hippel-Lindau Protein in Pancreatic β-Cell Function

Abstract: OBJECTIVE-TheVhlh gene codes for the von Hippel-Lindau protein (VHL), a tumor suppressor that is a key player in the cellular response to oxygen sensing. In humans, a germline mutation in the VHL gene leads to the von Hippel-Lindau disease, a familial syndrome characterized by benign and malignant tumors of the kidney, central nervous system, and pancreas. RESEARCH DESIGN AND METHODS-We useCre-lox recombination to eliminate Vhlh in adult mouse pancreatic ␤-cells. Morphology of mutant islets is assessed by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 49 publications
(42 reference statements)
5
91
1
Order By: Relevance
“…45,46 Indeed, previous studies have shown that hypoxia impairs insulin secretion. 52,53 Thus, these studies along with our findings and others, 27,41,42 which all show impaired b-cell function with VHL loss, are in contrast to the results by Gunton et al, 12 which suggests that a reduction in HIF expression in the islets contributes to the b-cell dysfunction in type 2 diabetes. 12 In the same study, it was reported that knockdown of HIF-1a in Min6 cells leads to impaired glucose-stimulated insulin secretion.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…45,46 Indeed, previous studies have shown that hypoxia impairs insulin secretion. 52,53 Thus, these studies along with our findings and others, 27,41,42 which all show impaired b-cell function with VHL loss, are in contrast to the results by Gunton et al, 12 which suggests that a reduction in HIF expression in the islets contributes to the b-cell dysfunction in type 2 diabetes. 12 In the same study, it was reported that knockdown of HIF-1a in Min6 cells leads to impaired glucose-stimulated insulin secretion.…”
Section: Discussioncontrasting
confidence: 55%
“…This is in keeping with other studies, which all show a defect in b-cell function as a result of VHL loss. 27,41,42 Importantly, however, these studies did not show a defect in b-cell mass. In contrast to these studies, we are the first to show that VHL has a critical role in b-cell growth that occurs with aging.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Conversely, increasing HIF-1α using iron chelation with DFO or DFS caused significant changes in gene expression, which differed from severe hypoxia or VHL deletion (46)(47)(48). DFS significantly improved glucose tolerance in mice receiving a highfat diet (HFD) but had no effect in β-Hif1a-null mice, demonstrating that β cell HIF-1α was required for its effect.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, we and others have reported that constitutive activation of HIF-1a, via deletion of VHL in b cells, also results in impaired glucose sensing and glucose stimulated insulin secretion. [13][14][15][16] While VHL signaling is complex and could have numerous effects in the b cell, these studies collectively suggest that both loss and constitutive activation of the HIF pathway leads to b cell dysfunction, however the specific role of HIF-2a, also known as endothelial PAS domain protein 1 (EPAS1), in regulating b cell function and glucose homeostasis is unknown.…”
Section: Introductionmentioning
confidence: 99%